The Classification of Digital Products in Digital Trade Rules Under the WTO - Yun Liu (Studies in Law and Justice, 2023)
The negotiation of WTO digital trade rules has been restarted as states have accelerated the promotion of digital trade legislation in recent years. The classification of digital products as “services” or “goods” will affect how GATT and GATS rules are applied. The existing digital trade rules and WTO rules do not clearly define digital trade product classification. Digital products have both the characteristics of “goods” and “services,” and special consideration should be given to the special characteristics and the impact on member states, particularly on the application of tariff exemption and non-discriminatory treatment, in order to take a more flexible approach to dealing with WTO digital trade negotiations.